Model pembelajaran bola basket berbasis permainan: Bagaimana peningkatannya terhadap keterampilan passing? - Rahmadani, Ahmad; Candra, Oki; Daharis; Khoeri, Ahmad (Edu Sportivo: Indonesian Journal of Physical Education, 2021)
This study aims to determine the improvement of basketball passing skills with a game-based approach. This study involved 10 students of the Department of Physical Education, Health and Recreation, Universitas Islam Riau. The method used is quasi-experimental. The research instrument used a basketball passing test which consisted of three phases: the initial phase, the main phase, and the follows through phase. The data analysis technique used t test for similar sample groups. Based on the results of data analysis, it can be explained that the average value of the pre-test was 9.6, while the average value at the time of the post-test increased to 10.6. There was an increase of 10.41% of the difference in the results of the pre-test and post-test. That means that based on the results of the research it is proven that by applying a game-based approach can improve basketball passing skills in students of the Department of Physical Education, Health and Recreation, Universitas Islam Riau.